Binder jet printing, spark plasma sintering studies on 420 stainless steel - Leong, Jarrat Jia Jun (Nanyang Technological University, 2020)
One of the classifications of Additive Manufacturing (AM) is Binder Jetting. It is the most preferred AM technology and has recognizable benefits among the 6 categories of AM technology. Binder jetting is special in a way which heat is not applied in the manufacturing process. The rest of the AM technologies uses thermal energy that will generate internal stress distribution locked into a material and it must be released in a secondary process after printing. Benefits of Binder Jetting comprises of printed parts free of residual stresses, support is not necessary, and lesser powder required. Nonetheless, Binder Jetting parts in the green state have poor mechanical properties and very porous. Spark Plasma Sintering is a method that requires only a couple of minutes to finish a sintering process instead of the traditional sintering that will take a few hours. Spark Plasma Sintering can produce high relative densities in just a few minutes and the grain growth size of nanopowders is significantly low after sintering. As such, the author has prepared specimens through the standard preparation procedures. Thereafter, the specimens were analyzed through various microscopes and hardness was measured through Vickers hardness test to compute the qualities of the specimens. In this study, 6 samples were tested out with 1) Heating rate of 100 and 200 (+k/min), 2) Cooling rate of 50 (-K/min) 3) 5 minutes holding time at sintering temperature, 4) Pressure of 3kN and 5) Sintering temperature of 600, 700 and 800°C. Another sample heated at 700°C for 5 hours in Box Furnace. Green part is cured under 200°C for 8 hours in curing oven with no special atmosphere. The study showcases the effect sintering temperature and heating rate affect the relative density, hardness and the grain growth size of the specimen. Unlike conventional furnace process where grain growth in Spark Plasma Sintering is much faster. Final grain growth in SPS significantly smaller than conventional sintering process.